Challenges and proposed solutions for more accurate serological diagnosis of equine infectious anaemia. (23rd February 2013) - Issel, C. J.; Scicluna, M. T.; Cook, S. J.; Cook, R. F.; Caprioli, A.; Ricci, I.; Rosone, F.; Craigo, J. K.; Montelaro, R. C.; Autorino, G. L.
Abstract : Serological diagnosis of equine infectious anaemia virus (EIAV) infections has depended mainly on the agar gel immunodiffusion test (AGIDT). This study documents the presence of EIAV genetic sequences in a number of persistently infected horses and mules whose serums were interpreted as negative/equivocal on AGIDT, but positive on more than one ELISA test and in immunoblot tests. Strategies designed to take advantage of the combined strengths of the ELISA and AGIDT are shown effective in a national surveillance program for EIA in Italy where 17 per cent (25/149) of the equids considered to be infected with EIAV on combined/comparative serological data had reactions in the AGIDT that were interpreted as negative or equivocal. These data document the benefits of using a three‐tiered laboratory system for the diagnosis of EIA. Although the ELISA‐first strategy introduces some confusing results, the discovery of up to 20 per cent more cases of EIA makes it compelling. In our opinion, it is better and more defensible to find two samples in 1000 with resolvable but falsely positive ELISA tests for EIA than to release two to three horses in 10, 000 with falsely negative test results for EIA (the rates seen in the Italian surveillance presented here).